Diagnostic yield from routine metabolic screening tests in evaluation of global developmental delay and intellectual disability. Issue 6 (19th December 2020) - Vallance, Hilary; Sinclair, Graham; Rakic, Bojana; Stockler-Ipsiroglu, Sylvia
Abstract: Global developmental delay and intellectual disability (GDD/ID) affect 3% of the paediatric population. Although inborn errors of metabolism (IEM) are not a common cause of GDD/ID, early therapeutic intervention can improve neurodevelopmental manifestations. In 2012, a first-tier test panel, including specialized metabolic and routine chemistry tests, was piloted to community-based paediatricians in British Columbia with aims to achieve earlier diagnosis of treatable IEM. Objective: The aim of this retrospective review was to evaluate the diagnostic yield from these first-tier tests in the 7 years before (2006 to 2012) and after (2013 to 2019) implementation at the community paediatrician level. Results: Prior and postimplementation diagnostic yield of an IEM from first-tier metabolic testing was 9 out of 986 (0.91%) and 11 out of 4, 345 children (0.25%), respectively. Disorders of creatine metabolism and organic acidurias were the most frequently established diagnoses in both time periods. No diagnoses were established through acylcarnitine copper/ceruloplasmin, lactate, or ammonia testing. Twenty out of 24 patients had specific neurological or other red flag signs in addition to GDD/ID. Four boys diagnosed with an x-linked creatine transporter defect (CTD) had speech-language delay as the most prominent finding. Conclusions: The expansion of first-tier metabolic testing to community-based paediatricians in BC did not yield an increase in IEM diagnoses. A modified first-tier test panel should be offered to patients with GDD/ID, neurologic, and/or red flag signs. Urine creatine testing in boys with speech-language delay warrants consideration to detect CTD.